PENINGKATAN PEMAHAMAN FIQIH MELALUI METODE SAINTIFIK DI SEKOLAH MENENGAH PERTAMA (SMP) TAHFIDZ AL-AMIEN PRENDUAN SUMENEP - Yaqin, Muhammad Nurul; Rendiansyah, Rendiansyah; Sutrisno, Andri (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
The scientific approach makes learning more active and not boring, students can construct their knowledge and skills through facts found in field investigations for learning. In addition, with learning based on this scientific approach, students are encouraged to be more capable in observing, asking, reasoning, and learning and obtained by students carried out with their own senses and minds, so that they are directly in the process of gaining knowledge. The approach in this study uses a qualitative approach, while the type of researcher used in the study is descriptive. The data sources in this study consist of primary data, namely principals, teachers, students. While secondary data is in the form of documents in SMP Tahfid Putra Al-Amien Prenduan Sumenep Madura. Data collection techniques include interviews, observation and documentation. Data analysis techniques with single case design techniques introduced by Miles and Hiberman are carried out starting from the process of data collection, presentation and verification. Based on the research, it can be concluded that the application of the scientific approach in fiqh learning with the observing stage, where in class the teacher provides lessons that must be observed and understood by students. The questioning stage, the teacher provides a trigger for students' critical thinking. Exploring, students learn to obtain real learning outcomes with experiments. Associating, students carry out a logical thinking process on empirical facts that can be observed to obtain conclusions. Finally communicating, where teachers are expected to provide ample opportunities for students to communicate. While the impact is that students are active in performing mandatory prayers and know the legal basis for mandatory prayers, students are active in reading and interpreting naqli arguments about mandatory prayers, active students in mentioning the conditions of prayer, active students in mentioning the pillars of prayer.